2005
DOI: 10.1161/01.hyp.0000171475.40259.d1
|View full text |Cite
|
Sign up to set email alerts
|

High Sodium Intake Increases Blood Pressure and Alters Renal Function in Intrauterine Growth–Retarded Rats

Abstract: Abstract-A suboptimal fetal environment increases the risk to develop cardiovascular disease in the adult. We reported previously that intrauterine stress in response to reduced uteroplacental blood flow in the pregnant rat limits fetal growth and compromises renal development, leading to an altered renal function in the adult offspring. Here we tested the hypothesis that high dietary sodium intake in rats with impaired renal development attributable to intrauterine stress, results in increased blood pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 35 publications
5
32
2
Order By: Relevance
“…A prenatal 5% protein diet also produced offspring that were salt sensitive as adults (45), although others have reported that protein under-nutrition did not produce salt sensitivity (25). Finally, uterine artery ligation during the final week of pregnancy also produced adult offspring that increased blood pressure significantly when given 2% NaCl to drink (34). In the present investigation we used a HS challenge to test the hypothesis that a prenatal HS diet could also program salt sensitivity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A prenatal 5% protein diet also produced offspring that were salt sensitive as adults (45), although others have reported that protein under-nutrition did not produce salt sensitivity (25). Finally, uterine artery ligation during the final week of pregnancy also produced adult offspring that increased blood pressure significantly when given 2% NaCl to drink (34). In the present investigation we used a HS challenge to test the hypothesis that a prenatal HS diet could also program salt sensitivity.…”
Section: Discussionmentioning
confidence: 83%
“…Sprague-Dawley rats are not genetically salt sensitive, that is, a HS diet produces only a modest increase in blood pressure (15,28). However, there is some indication that perinatal HS and other models of fetal programming may impart a significant permanent salt sensitivity (8,34,45). The final hypothesis addressed was that a maternal HS diet limited to the period of pregnancy would produce offspring that were salt sensitive as adults.…”
mentioning
confidence: 99%
“…In addition, increased glomerular apoptosis has been observed (Pham et al 2003). Studies of the mechanism by which intrauterine growth retardation may induce hypertension have suggested a role for the renin-angiotensin system, renal sympathetic activation, maternal glucocorticoid and fetal kidney 11beta-hydroxysteroid dehydrogenase type 2 activation, and increased sodium retention (Baserga et al 2010;Ojeda et al 2007;Grigore et al 2007;Langley-Evans 1997;Sanders et al 2005;Franco et al 2012). Several studies have indicated that altered gene expression may be the result of epigenetic regulation (Baserga et al 2010;Pham et al 2003;Woroniecki et al 2011).…”
Section: Fetal Origins Of Adult Diseasementioning
confidence: 99%
“…LBW adults with low nephron number are prone to nnicroalbuminuria, proteinuria, and decreased glomerular filtration (Celsi et al, 1998;Nwagwu et al, 2000;Sanders et al, 2005). Thus, it is likely that intrauterine factors, including PAHs, compromise renal development resulting in low nephron number.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanism IOf fetall programming in hypertension, renal disease, and glomerulalr filtration. Intrauterine factors, including PAHs, compromise renal development resulting in low nephron number (Celsi et a/., 1998;Nwagwu et al, 2000;Sanders et al, 2005 . Using a metanephric kidney organ culture system, we have shown that exposure to BaP, a hydrocarbon ligand for the AHR, inhibits nephrogenesis and increases -KTS/+KTS WT1 mRNA ratios.…”
Section: Discussionmentioning
confidence: 99%